Computational phase diagrams for the Nd-based magnets based on the combined ab initio/CALPHAD approach. (September 2018) - Abe, Taichi; Chen, Ying; Saengdeejimg, Arkapol; Kobayashi, Yoshinao
Abstract: Sintered magnets hold a high amount of oxygen because of the strong affinity of oxygen with lanthanide elements, where oxygen forms variety of stable and metastable oxide phases. In order to control microstructures, which can affect magnetic properties, it is important to understand how oxygen behaves during the fabrication processes. A combined ab initio /CALPHAD approach was employed to estimate the phase equilibria with oxygen in microstructures of the magnets. It is demonstrated that this approach is efficient for systems in which available experimental and theoretical thermodynamic information is limited. Graphical abstract: Unlabelled Image